THE RELATIONSHIP BETWEEN WATCHING STRUCTURED CARTOON FILM WITH TODDLER CHILDREN'S SPEECH ABILITY AT RT. 003 RW. 001 CIBITUNG SUB-DISTRICT, WANASARI SUB-DISTRICT YEAR 2023 - Sandia, Tiara; Kristiani Gea, Nurti Yunika; Simamora, Rotu Suriany (Jurnal Medicare, 2023)
Background: Age 1-3 years, children at this age have several characteristics in common with the previous period. Physically the child is still experiencing rapid growth. Speech and language skills in early childhood are very important because they are not only a means of communication but also for the growth and development of children. children who since childhood are trained and guided to speak well. Watching structured cartoon films can affect children's speech development. So from watching movies that are structured with sufficient time limits, children will quickly grasp the language in cartoons because these cartoons are interesting spectacles for children. Research Objectives: Knowing the Relationship between Watching Structured Cartoon Films and Speaking Ability of Toddlers in Rt 003 Rw 001 Cibitung District, Wanasari Village Research Methods: The research method used is quantitative, with a research design that is observational analytic and uses a cross sectional approach. The population in this study were toddlers who had good speech skills in Rt 003 Rw 001, Cibitung District, Wanasari Village with a total of 80 children. The data collection technique uses simple random sampling. Research Results: It was found that with a significant level of 95% or an α value of 5% (0.05) the results of the Ci Square test obtained a p value (0.000) <α value (0.05). This shows that H0 is rejected. Conclusion: There is a relationship between watching structured cartoon films and the speaking ability of toddlers in RT 003 RW 001, Cibitung District, Wanasari Village. Keywords: Watching Structured Cartoon Movies, Speaking Ability